A case report on successfully treated invasive pulmonary mucormycosis in a patient with poorly controlled diabetes mellitus - P. Dikshaladevi; N. Selvaratnam; J. Nalayini; T. Peranantharajah (Asian Journal of Internal Medicine, 2024)
Although fungal infections are common in clinical practice, usually they are superficial and invasive infections are very rare among immunocompetent people. Invasive fungal infections in immunocompromised people are life threatening if left untreated. Among invasive fungal infections, mucormycosis is uncommon. Pulmonary mucormycosis is rarely seen in clinical practice and is often life-threatening. This case report describes a patient with poorly controlled diabetes who presented with pulmonary mucormycosis and responded well to systemic antifungals.